Throughput scaling by spatial beam shaping and dynamic focusing - Kumkar, M.; Kaiser, M.; Kleiner, J.; Flamm, D.; Grossmann, D.; Bergner, K.; Zimmermann, F.; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
With availability of high power ultra short pulsed lasers, one prerequisite towards throughput scaling demanded for industrial ultrafast laser processing was recently achieved. We will present different scaling approaches for ultrafast machining, including raster and vector based concepts. The main attention is on beam shaping for enlarged, tailored processed volume per pulse. Some aspects on vector based machining using beam shaping are discussed. With engraving of steel and full thickness modification of transparent materials, two different approaches for throughput scaling by confined interaction volume, avoiding detrimental heat accumulation, are exemplified. In Contrast, welding of transparent materials based on nonlinear absorption benefits from ultra short pulse processing in heat accumulation regime. Results on in-situ stress birefringence microscopy demonstrate the complex interplay of processing parameters on heat accumulation. With respect to process development, the potential of in-in-situ diagnostics, extended to high power ultrafast lasers and diagnostics allowing for multi-scale resolution in space and time is addressed.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Beam shaping; Laser; Materials processing; Nonlinear absorption; Pump-probe; Ultra-short pulse